Cattywampus - Van Otterloo, Ash (Scholastic Inc., 2022)
Even though magic is forbidden in her family, twelve-year-old Delpha McGill wants to use it to help her mother, who is drowning in bills. Twelve-year-old Katybird Hearn is intersex and is desperate to use magic, afraid that being born with XY chromosomes means that she can't use her family's magical abilities. When the two accidentally wake up a graveyard of long-dead warring witches from their families thanks to a spell gone bad, the two must race against time and their fellow townspeople in order to get rid of the zombies.